Correlations between Fragmentation of Farms in the Republic of Moldova and its Impact on Farm Incomes Compared to Poland and Romania - Popa, Daniela; Dinu, Toma (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2015)
The paper presents selected problems of farm management in terms of fragmented agriculture. The problem of land fragmentation was exemplified in these three countries of Central and Eastern Europe. The main purpose of the study was to compare the effectiveness of selected indicators of agricultural production in the three selected countries. For the analysis, the data on the concentration indexes was selected from: Lorenz concentration coefficient, the Gini index, and territorial concentration coefficient (Gini C and Stuck formula). In selected countries, there are a large number of small and very small farms. They represent the majority of farms managed by private owners. To a large extent, they are called semi-subsistence farms or social farms. Some of them provide part of their products on the market. Small farms are part of the so-called European Model of Agriculture – a model that consists of small family farms. It is difficult to indicate a correct definition of “small farm”, as it may be defined differently depending on the region or country. In the EU, small farms occupy a dominant position, being a constant subject of debates and policy. The authors of the article stressed the need for strengthening the small farm position, for example by enlarging their acreage or by initiating horizontal or vertical cooperation in a way that shall not impair the role of small farms. They are important in biodiversity protection, preserving the rural landscape, as well as maintaining local tradition, culture and heritage.